Collaborative m-learning practice using Educ-Mobile - Herrera, Susana Isabel; Sanz, Cecilia Verónica (2014)
A collaborative m-learning experience conducted at higher education in the Northwest of Argentina is described in this article. It was implemented in a postgraduate course using Educ-Mobile, an interactive mobile game. The educational practice was designed using the framework for the Analysis, Design and Assessment of m-learning Experiences (MADE-mlearn). This framework allows the analysis and assessment of existing m-learning experiences and the design of new ones. The results of this experience, considering both learning outcomes and students’ satisfaction using the application, are presented. To expand the scope of Educ-Mobile to other specific domains and to elementary and high schools is one of the most important objectives of the authors in the future.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on Collaboration Technologies and Systems (2014 may. 19-23 : Minneapolis, Estados Unidos)
Keywords: EDUCACIÓN; aprendizaje móvil